Optical and Microwave Dielectric Properties of Phase Pure (K0.5Na0.5)NbO3 Thin Films Deposited by RF Magnetron Sputtering. Issue 5 (28th February 2015) - Peddigari, Mahesh; Sindam, Bashaiah; Raju, K.C. James; Dobbidi, Pamu
Abstract : (K0.5 Na0.5 )NbO3 (KNN) thin films have been deposited onto Pt/Ti/SiO2 /Si and quartz substrates by RF magnetron sputtering. The films were deposited at 400°C with the variation in oxygen mixing percentage (OMP) ratio from 0% to 100% and annealed at 700°C in oxygen atmosphere. The crystallinity of the films is found to be increased with increased OMP. Dielectric properties of the films were examined over the frequency range from 1 kHz to 1 MHz and the temperature range of 30°C to 400°C. The Curie temperature of the films was found to be in the range 369°C–373°C. For the first time, the split postdielectric resonator (SPDR) method was used to measure the microwave (10–20 GHz) dielectric properties of KNN thin films. The optical properties of as‐deposited and annealed KNN thin films were investigated by means of transmittance spectra. The optical bandgap is calculated by using the Tauc relation, and found to be in the range 4.34–4.40 eV and 4.29–4.37 eV for the as‐deposited and annealed films, respectively. The refractive index ( n 700nm ) of the films found to be in the range 1.98–2.01 and 1.99–2.07 for as‐deposited and annealed films, respectively. The refractive index dispersion is analyzed by using Wemple–DiDomenico (W–D) single‐oscillator model. The effect of annealing and OMP on the refractive index, packing density and W–D parameters has been investigated. The average single oscillator energy ( E o ) and dispersion energies ( E d ) of the annealed KNN thin films are in the range of 6.17–7.16 eV and 18.77–22.19 eV, respectively. AC‐conductivity of the annealed films was analyzed by using double power law. Ag/KNN/Pt thin films followed the ohmic conduction ( J  ∝  E α, where α ~1) and the low leakage current density obtained for the deposited at 100% O2 is 3.14 × 10 −5  A/cm 2 at 50 kV/cm.